Delayed Diagnosis of Postintubation Tracheal Stenosis due to the Coronavirus Disease 2019 Pandemic: A Case Report. Issue 8 (June 2020) - Ramalingam, HariPrasad; Sharma, Ankur; Pathak, Vinay; Narayanan, Balakrishnan; Rathod, Darshana Kirtikumar
Abstract : Tracheal stenosis is an uncommon but severe problem after long-term intubation. Here, we report a patient who came from a containment zone of coronavirus disease 2019 (COVID-19) and presented with complaints of breathlessness and cough. She was suspected to have an infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Later, she developed type 2 respiratory failure and carbon dioxide narcosis because of delay in diagnosis of severe, near-complete postintubation tracheal stenosis due to over suspicion of COVID-19 during the current pandemic.